Pendidikan Agama Islam: Pengertian, Tujuan, Dasar, dan Fungsi - Hilda Darmaini Siregar; Zainal Efendi Hasibuan (STIKes Ibnu Sina Ajibarang, 2024)
The progress of a nation is supported by complete human resources with three important elements; healthy, intelligent and of good character. However, the dream of advancing the nation will only become a dream when phenomena that show bad character increasingly emerge in this country, and the most worrying thing is that students are involved in it. In this position, educational failure is an area that is often the subject of discussion, and especially religious education is increasingly becoming the main focus. In the midst of the hegemony of discussions about materials, models and environmental creation in contemporary conditions, this article aims to retrace the concept of PAI as a whole, including its meaning, objectives, foundations and functions, so that various PAI activities, especially in schools, do not deviate from its sermons. . Literature review was chosen as a method for examining the writings of figures, book and journal authors, as well as regulatory documents related to education and PAI. The results of the study show that there are three words that are often discussed by figures when exploring the concept of education in Islam, namely tarbiyah, ta'dib, and ta'lim. These three words are the basis for exploring the concept of PAI as a whole in Indonesia. PAI has colored the education process in Indonesia, with Islamic teachings as the content taught. By paying attention to its basis and function, PAI in schools must be taught by professional PAI teachers with the aim of educating, guiding and directing students to become Islamic individuals (insan kamil; faithful, obedient and moral) within the framework of students as individuals, family members, members of society, citizens and citizens of the world. This point also emphasizes that PAI's goal is not to make students become experts in Islamic religion. This article can provide insight, especially to teachers or PAI study program students, in understanding PAI as a whole, especially its relation to schooling.